Performance enhancement of photovoltaic modules by nanofluid cooling: A comprehensive review. (3rd March 2020) - Kumar, Rajan; Deshmukh, Vipul; Bharj, Rabinder Singh
Summary: Only 15‐20% of solar radiation incident on the photovoltaic (PV) cells is utilized which further reduces due to the rise in the temperature of the PV module and it also degrades the lifespan of the PV module. Therefore, numerous attempts were made to reduce this rising temperature of the PV module and different cooling techniques were employed. Nanofluid cooling is one of the potential cooling techniques for lowering the temperature of the PV module and augmenting the heat transfer by increasing the thermal conductivity of the nanofluid relative to the base fluid (BF). The experimental and numerical studies related to the cooling of PV cells with nanofluids have been reviewed. It was found that the heat transfer from the back of the PV module is enhanced with the augmentation in the concentration of nanoparticle in BF; however, some studies also demonstrate that the enhancement in the heat transfer also depends upon other factors such as the geometry at the rear of the PV module, nanoparticle material, nanoparticle size, BF, ambient conditions, etc. This review article also demonstrates the various issues with nanofluids such as instability, technological difficulties, high system costs, and the impossibility of finding a viable operational design which creates a barrier in the commercialization of the nanofluid cooling technique for PV modules.